Computer program enhances guidelines for gas-liquid separator designs - COKER, A. K (The Oil & gas journal, 1993)
Designers are often required to size separators or knockout drums for removing liquids from process gas streams. A FORTRAN computer program called 'Vessel' has been developed to size both horizontal and vertical separators for known fluids' rates and physical properties. Following a review of the design of both horizontal and vertical separators of both knockout drum and demister separator type, the separator sizing programs are presented.